The damages of bearing construction in not conserved buildings and the research into their suitability for future exploitation - Dulinskas, Eugenijus; Jarmolajev, Andrej; Jokūbaitis, Vidmantas; Jurkenas, Gintaras; Kairyte, Lolita; Šaučiuvenas, Gintaras; Šneideris, Arnoldas; Vainiūnas, Povilas (Technological and Economic Development of Economy, 2004)
There are frequent cases when load‐bearing reinforced concrete structures of not completed buildings are directly exposed to precipitation (rainfall, snowfall) and to environment of positive and negative temperature. Multihollowcore concrete slabs are especially vulnerable to such actions since investigations of condition of non‐conserved buildings indicate that these slabs can crack critically. Water accumulated in hollows of slabs and frozen under negative temperature can split concrete in vertical walls between hollows, inflict concrete cracking below hollows or spalling of large sections together with longitudinal reinforcement in them at the bottom of slabs. In performed investigations of condition of non‐completed and non‐conserved load bearing structures a modern method was employed for the determination of cracking in walls between hollows of slabs, using mini video‐camera. Analysis of cracking in slabs indicated that the character of cracking is governed by the quantity of water accumulated in a hollow at the moment of freezing and the level of freezing water in adjacent hollows of a slab and the compaction quality of concrete in a tensile zone of a slab as well. The analysis of pressure on the surface of hollows developed by ice set can be analysed employing a model of non‐linear analysis of COSMOS/M program and fracture mechanics of solids. Several versions of cracking in multihollowcore concrete slabs are possible, the most critical one of which is when a part of a bottom flange of a slab together with longitudinal reinforcement spalls off due to normal and shear deformations. The accomplished analysis allowed to establish kinetics of cracking for slabs and to evaluate their condition more reliably.Article in Lithuanian.Nekonservuotų pastatų laikančiųjų konstrukcijų pažeidimai ir jų tinkamumo tolesnei eksploatacijai tyrimaiFirst Published Online: 21 Oct 2010